Pentingnya Menjamin Penerapan Prinsip “Enam Benar” Pemberian Obat Guna Meningkatkan Keselamatan Pasien di Rumah Sakit - Nursery, Septi Machelia Champaca; Lucia Andi Chrismilasari (LPPM Universitas Palangka Raya, 2024)
The role of nurses in the medication process involves administration, monitoring drug responses, and educating patients. Mistakes in medication administration can lead to toxic effects on patient health, such as drug poisoning, drug allergies, vomiting, and even death. Therefore, nurses are a critical factor in the success of treatment in healthcare services, especially in hospitals. Various efforts have been made to reduce the incidence of medication errors, including the implementation of safe medication administration principles. Research by Nursery, Septi (2023) revealed observational data regarding patient identification during medication administration. It was found that, at the time of drug administration, 50% of nurses did not identify the patient, three nurses (30%) called out the patient’s name without checking the identification wristband, and two nurses (20%) correctly identified the patient by checking the wristband. Observations related to the principle of correct medication showed that four nurses (40%) did not explain to the patient what medication was being given. Regarding the principle of correct dosage, it was noted that three nurses (30%) were not accustomed to calculating dosages using formulas and tended to guess instead; two nurses (20%) calculated dosages by asking colleagues, while five nurses (50%) were skilled in calculating dosages. Nurses responsible for administering injections relied solely on a staff logbook and did not document the information immediately in the patient status book. Out of 15 patient status books reviewed, only 9 (60%) were fully completed by nurses, while 6 (40%) were not filled out completely. The research findings indicate that career advancement, including work experience and the education level of nurses, significantly influences the implementation of the